1984
DOI: 10.1210/endo-114-3-753
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of Inhibitors of Hormone Processing on Insulin Action in Isolated Hepatocytes*

Abstract: Several compounds known to alter receptor-mediated endocytosis were tested for their effect on insulin action in isolated rat hepatocytes. Dansylcadaverine blocked the inhibitory effect of insulin on hepatic protein degradation, but was without effect on the inhibition produced by high concentrations of amino acids. Dansylcadaverine also was without effect on the stimulatory action of insulin on glucose incorporation into glycogen, but totally blocked the insulin stimulation of alanine uptake. No inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 43 publications
3
28
1
Order By: Relevance
“…In the CHO cells investigated in this study, we have demonstrated a similar marked inhibition of ligand-induced IGF-I receptor internalization at 15Ā°C. Previous studies have shown that dansylcadaverine appears to inhibit a step in endocytotic vesicle formation that involves the pinching off of vesicles from the plasma membrane (33,37). Based on these sites of inhibition, our findings are consistent with a model in which the tyrosine phosphorylation of Shc occurs predominantly by activated IGF-I receptors in endosomes, or at least by receptors in vesicles that have moved past the point in the endocytotic pathway inhibited by dansylcadaverine.…”
Section: Discussionsupporting
confidence: 90%
“…In the CHO cells investigated in this study, we have demonstrated a similar marked inhibition of ligand-induced IGF-I receptor internalization at 15Ā°C. Previous studies have shown that dansylcadaverine appears to inhibit a step in endocytotic vesicle formation that involves the pinching off of vesicles from the plasma membrane (33,37). Based on these sites of inhibition, our findings are consistent with a model in which the tyrosine phosphorylation of Shc occurs predominantly by activated IGF-I receptors in endosomes, or at least by receptors in vesicles that have moved past the point in the endocytotic pathway inhibited by dansylcadaverine.…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of rat hepatocyte insulin clearance and degradation has been shown to impair the action of insulin on amino acid but not glycogen metabolism [39]. The biological significance of decreased hepatic insulin clearance for hepatic metabolism in the normal glucose tolerant relatives requires further study, although it is interesting to note that hepatic glucose output was found to be normal in a group of comparable relatives of NIDDM families [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo and in vitro investigations have provided substantial evidence for a relationship between insulin action and intracellular processing of insulin and its receptor (Ferrannini et al, 1982;Flier et al, 1982;Peavy et al, 1984;Veda et al, 1985;Jochen and Berhanu, 1987;Miller, 1988). Furthermore, it has been suggested that abnormalities in insulin receptor recycling and intracellular processing of the insulinreceptor complex might contribute to impair insulin action in patients with type 2 diabetes mellitus (Jochen et al, 1986;Grunberger et al, 1989;Trischitta et al, 1989;Benzi et al, 1990Benzi et al, , 1997Sesti et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, most of the internalized receptor is recycled to the cell surface to be reutilized, and only a small fraction is degraded (Marshall, 1985b). Several lines of evidence suggest that internalization and intracellular processing of the insulin-receptor complex may play a role in insulin action (Peavy et al, 1984;Veda et al, 1985;Jochen and Berhanu, 1987;Miller, 1988). Association between impaired in vivo insulin clearance and action have been reported in subjects with insulin resistance (Ferrannini et al, 1982;Flier et al, 1982).…”
mentioning
confidence: 99%